A review of antioxidant activity in oil palm (Elaeisguineensis) extract and refined palm oil / Arnasil Julakjam - Julakjam, Arnasil (Faculty of Plantation and Agrotechnology, 2016)
Oil palm is rich with phytonutrients such as carotenoids, tocols, sterols, phenolic compound, squalene and coenzyme Q. The carotenoids, tocols, sterols and this phenolic compolmd are known to exhibit natural antioxidant properties. Depletion of antioxidant enzymes is known to increase the risk of complication such as cardiovascular disease, diabetes and cancer. Thus, in order to investigate such effects of antioxidant properties in palm oil, we have reviewed the antioxidant agent present in the extraction of oil palm such as oil palm leafs extract COPLE), oil palm fresh fruit / FFB and refined palm oil after deep frying. Most of the finding revealed oil palm totally contains antioxidant compound that helps to reduce free radical.